The Analysis of Traangle Fraud Factors to Fraudulent Financial Statement - Dewi Susanti (BPJP - STEI, 2018)
This This research aims to analyze the fraud triangle against fraudulent financial statement. Based on research conducted [13] et al., This study developed a variable of the fraud triangle that can be used,namely the pressure is proxied by financial stability (AGROW), external pressure (LEV) and financial targets (ROA). Opportunities are proxied by ineffective monitoring (IND). And rationalization proxied by the change of auditors (AUDCHANGE). While fraudulent financial statements are measured by [2] Score. The population in this research was manufacturing companies in 2012-2014 listed in the Indonesia Stock Exchange. Companies that take into population is 152 companies, while the research sample was 47 companies and a number of observations made during the years 2012-2014 is 141 items, observations. Statistical tests showed that empirically variable pressure proxied by financial stability (AGROW) has a significant positive effect on the level of risk of fraudulent financial statements. While variable pressure is proxied by external pressure (LEV) and financial targets (ROA) has positive and negative influences were insignificant. Opportunities are proxied by ineffective monitoring (IND) have no significant negative influence. And rationalization is proxied by the change of auditors (AUDCHANGE) had no significant positive effect.